ADAB GURU TERHADAP MURID PERSPEKTIF IMAM AL-GHAZALI DI DALAM KITAB BIDĀYAH AL-HIDĀYAH - Ramli, Muhamad; Sayuti, Ahmad (Program Studi PAI STAI Al Falah Banjarbaru, 2022)
Abstract: This study aims to determine the concept of teacher etiquette towards students from the perspective of Imam al-Ghazali in the Bidāyah al-Hidāyah book and its relevance to the current educational context. This type of research is library research, with data collection through documentation techniques. This research was conducted with a qualitative descriptive approach and using content analysis techniques. Based on the results of the study, the concept of a teacher's adab towards students from Imam al-Ghazali's perspective there are fourteen, namely: Iḥtimāl (ready to bear the burden), al-Ḥilm (being polite), being seated with authority, avoiding arrogance, being Tawāḍu' ( humble), not fond of playing games and joking, gentle to students, guiding students with low IQ to the maximum, not scolding students with low IQ, not ashamed to say